Finding Exact Bright Soliton Solutions for Generalized Burgers-Huxley Equation with Constant Coefficients - Karroum, Ramez (Latakia University Journal -Basic Sciences Series, 2019)
The aim of this research is to present exact analytical bright soliton solutions for generalized Burgers-Huxley equation with constant coefficients by using the solitary wave ansatz method. Necessary conditions for existence of this solutions are presented. The graphs that the wave is soliton and bright and is moving to the right as time changes, It also shows the effect of the coefficient on the amplitude of this wave. The study shows that the using method is efficient to give this kind of solutions for the nonlinear partial differential equations.